2007
DOI: 10.1258/096914107782066185
|View full text |Cite
|
Sign up to set email alerts
|

Newborn sickle cell disease screening: the Jamaican experience (1995–2006)

Abstract: Objectives: The aim of this study was to evaluate the existing newborn sickle haemoglobinopathy screening programme in Jamaica. Methods: A retrospective analysis of infants screened during the period 8 November 1995 to 22 July 2006 was performed. Patient data for analyses was restricted to patients with homozygous (Hb SS) sickle cell disease. Published data from the Jamaican Sickle Cell Cohort Study was used to make comparisons with the study sample. Results: The study sample consisted of 435 patients with H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
1
11

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(99 citation statements)
references
References 13 publications
3
84
1
11
Order By: Relevance
“…Similar incidence (8.2 and 9.2 first episodes per 100 patient-years) was found by other authors. 8,23 Regarding recurrence of episodes, the results from other authors are similar to those found in our study, with rates of 49, 50 and 71%. 8,13,14 There was no statistically significant association between sex and development of ASS, similar to the findings by other authors.…”
Section: Discussionsupporting
confidence: 91%
“…Similar incidence (8.2 and 9.2 first episodes per 100 patient-years) was found by other authors. 8,23 Regarding recurrence of episodes, the results from other authors are similar to those found in our study, with rates of 49, 50 and 71%. 8,13,14 There was no statistically significant association between sex and development of ASS, similar to the findings by other authors.…”
Section: Discussionsupporting
confidence: 91%
“…Data from the Jamaica Sickle Cell Cohort Study show that approximately 14% of the SCD children died in the first two years of life before early-age interventions had been implemented, while 32% and 61% of children with haemoglobin SS disease became symptomatic by age of one year and two years respectively. 24,25 Such improvements in the screening coverage rate and early inclusion of affected children were a direct consequence of the centralized management of the UNBS programme, with close relationships between the reference diagnosis laboratory and the sickle cell centre (the laboratory was a unit of the sickle cell centre until 2011; now both are located in the same building). This allows earlier pathology results to be available to the nurse coordinator, and ensures timely enrollment of the affected children.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence clearly highlights the benefits of NBS, enrolment into a comprehensive care programme and implementation of simple interventions such as penicillin prophylaxis (3,5,12). Such services are essential in countries like Jamaica where the burden of disease is high compared to other countries.…”
Section: What Lies Aheadmentioning
confidence: 99%
“…In addition, survival estimates in the childhood period show improvement when compared with the Jamaica Sickle Cell Cohort Study (3). Overall mortality in children 10 years and under decreased from 17.6% in the Jamaica Sickle Cell Cohort Study to 1.8% in the JamSCUB cohort (3).…”
Section: Introductionmentioning
confidence: 99%